PENERAPAN TEKNIK MODIFIKASI PERILAKU DALAM MENINGKATKAN SEMANGAT BELAJAR ANAK SELAMA “STAY AT HOME” - Aufa Melia Mareta (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2020)
The spirit of learning in children during COVID-19 is a challenge that is present for teachers and parents. This paper aims to provide a brief description of how behavior modification techniques namely fading, economic tokens, and shaping provide solutions in shaping, maintaining, and enhancing children's enthusiasm for learning during